(untitled) (Journal of Shaheed Suhrawardy Medical College, 2022)
Objective: To analyze the autopsy findings in the cases of fatal head injuries due to road traffic accidents. Study Design : Retrospective study Place and duration of study: This study was conducted at the Rangpur Medical College morgue among victims of road traffic accidents (RTA) during the period of July 2014 to June 2016. It was conducted to ascertain the patterns of fatal head injuries due to road traffic accidents as documented during autopsies performed at Rangpur Medical College during (July 2014 to June 2016) the two years. Material & Methods: Road traffic accident are the major causes of death worldwide. Head injuries is the single most common cause of mortality in road traffic accidents; head injuries being the most vulnerable part of the body. Total74 victims were taken from the road traffic accidents and died due to head injury. Aim of the study to find out the patterns of head injuries, their age and site distribution of different type of fractures. Results: The cases were seen more in the male victims (87.84%) as compared to female (12.16%). Present study showed that the place of occurrence of road traffic accident was more in the urban areas (77.03%) as compared to rural areas (22.97%). No one of the threewheeler riders was wearing helmets at the time of accidents. We observed subdural hemorrhage (SDH) in 63.83% followed by sub arachnoid hemorrhage (SAH) in 27.66% intracranial hemorrhage (ICH) 6.38% and least was extradural hemorrhage (EDH) 2.13% in twowheeler riders. while in three-wheeler riders SDH in 51.85% followed by SAH in 29.63% ICH in 11.11% and least was EDH in 7.41% in cases where skull fracture occurred. Most of the accident occurred at night. Conclusion: Head injury is one of the important causes of death in road traffic accidents. Most of the deaths occur on spot before any life support can be given to these subjects. The pattern of skull fractures observed in this study was quite comparable to other studies. It indicates that road traffic accidents lead to similar kinds of fatal head injuries throughout the world. J Shaheed Suhrawardy Med Coll 2021; 13(1): 75-79